Integrated Analysis of Stemness-Related LncRNAs Helps Predict the Immunotherapy Responsiveness of Gastric Cancer Patients - Jiang, Quan; Chen, Lingli; Chen, Hao; Tang, Zhaoqing; Liu, Fenglin; Sun, Yihong (Frontiers in Cell and Developmental Biology, 2021)
The immune microenvironment plays a critical role in tumor biology. As a critical feature of cancers, stemness is acknowledged as a contributor to the development of drug resistance in gastric cancers (GCs). LncRNAs have been revealed to participate in this process. In this study, we aimed to develop a stemness-related lncRNA signature with guiding significance for immunotherapy. Three cohorts (TCGA, Zhongshan and IMvigor210) were enrolled for analysis. A list of stemness-related lncRNAs (SRlncRNAs) was collected by coexpression strategy under the threshold of coefficient value > 0.35 and p value < 0.05. Cox and Lasso regression analysis was further applied to find out the SRlncRNAs with prognosis-predictive value to establish the stemness-related lncRNA signature (SRLncSig) in TCGA cohort. IPS and TIDE algorithms were further applied to predict the efficacy of SRLncSig in TCGA and Zhongshan cohorts. IMvigor210 was composed of patients with clinical outcomes of immunotherapy. The results indicated that SRLncSig was not only being confirmed as an independent risk factor for GCs, but identified as robust indicator for immunotherapy. The patient with lower SRLncSig score was more likely to benefit from immunotherapy and the results were highly consistent in 3 cohorts. In conclusions, our study could not only clarify the correlations between stemness and immunotherapy in gastric cancer patients, but also provided a model to guide the applications of immunotherapy in clinical practice.